Analysis of the Sustainability of Healthy Plant Cultivation in Rice Commodity (Case Study in Wlingi District, Blitar Regency) - Nurul Catur Febriana; Soemarno Soemarno; Hartati Kartikaningsih (Postgraduate School Universitas Brawijaya, 2022)
The high demand for rice increases the chances of intensive rice cultivation (2 to 3 times a year). If these cultivation activities are not managed properly, it can reduce the quality of rice cultivation land due to ecosystem imbalances. Responding to this challenge, the Directorate of Food Crops Protection is present through the Healthy Plant Cultivation program as an alternative to rice cultivation techniques that are environmentally friendly and sustainable. A quantitative approach is used in this research. This study aims to analyze the sustainability of healthy rice farming in Wlingi District, Blitar Regency. The method used is Multidimensional Scaling (MDS) analysis. The value of the sustainability of healthy rice farming in Wlingi District as measured from the economic, ecological, social, technological, and institutional dimensions indicates a